EVALUASI KELAS JALAN PADA RUAS JALAN SAMBOJA - SEPAKU PROVINSI KALIMANTAN TIMUR - ROHMAN, TAUFIK (KURVA S JURNAL MAHASISWA, 2014)
Connecting road between Kutai Kartanegara regency with Penajam Paser Utara, exactly roads Simpang KM. 38 Samboja - Sepaku that makes this path as the liaison to the South Kalimantan Province. This road conditions many are not intact or there is some damage to roads, be it in a state of corrugated, perforated or peeled asphalt. When viewed from the daily activities, this road is a favorite route for large vehicles for the mobilization of heavy equipment such as excavators both directions Samboja to Sepaku and vice verse. Based on the above conditions to determine the damage that occurs the need for in-depth analysis about the load received by the road. With the 2 method is applied that AASHTO 1993 Method and SNI 1732-1989-F Method to determine how much the value of the load received by the road. The research is in the area of Kutai Kartanegara Regency and Penajam Paser Utara Regency, on the road Simpang KM. 38 Samboja - Sepaku. Analyze and calculate the volume of LHR and ESAL value, LER value and MST value during the life of the plan and the current research on road Simpang KM. 38 Samboja - Sepaku. Methods of data collection techniques for this study consisted of primary data and secondary data. By calculating LHR during the life of the plan compared with the data of actual LHR, and then calculated each load received by the road. Calculation spelled out in detail the steps that have been prepared according to the basic theory. Calculation consists of AASHTO 1993 Method for ESAL values and SNI 1732-1989-F Method for LER value. Results of calculation has been obtained that the volume LHR at the time the study was 2.014 vehicle/day, ESAL value is AASHTO 1993 Method at the time of the study amounted to 4.151.777,485 and during the design life of 1.487.137,753. LER value SNI 1732-1989-F Method at the time of the study amounted to 270,2956 and during the life of the plan amounted to 229,7872. While MST value proper for the life of the plan amounted to 112.830,088 (AASHTO 1993 Method) and amounted to 8,2288 (SNI 1732-1989-F Method) and the actual of MST value 161.945,878 (AASHTO 1993 Method) and amounted to 9,6794 (SNI 1732-1989-F Method).